Sistem Pakar Fuzzy Untuk Optimasi Penggunaan Bandwidth Jaringan Komputer - Mustaziri, Mustaziri (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
The need for bandwidth availability today is very high along with the increase of infrastructural growth of internet network. Therefore, the presence of efficient, reliable, and economical service availability system is required. It can be achieved byperforming  good  and  appropriate  system  planning.  In  providing  efficient  and  reliable  internet  services,  one  of  the supporting factors is the optimization of bandwidth using. To optimize the use of bandwidth, we use fuzzy expert system by Sugeno method. This fuzzy expert system use 3 input variables, such as lecture room, day, and t ime, with one output variable of the capacity of bandwidth used. Rule base being made based on the consultation with the expert to determine the rule base for fuzzy  system input.  The computation to determine the average error using the computation formula  of MAPE  (Means  Absolute  Percentage  Error)  which  is  the  error  median  of  absolute  percentage.  The  data  of  the  research results on the optimization of bandwidth using in fuzzy expert system with Sugeno method obtain from verification, that is by comparing actual data to prediction data with fuzzy system. The average error result is 6,5142 %.Keywords: Fuzzy Expert System; Optimization; Bandwidth